2013
DOI: 10.1371/journal.pone.0061267
|View full text |Cite
|
Sign up to set email alerts
|

EGFR-Targeted Granzyme B Expressed in NK Cells Enhances Natural Cytotoxicity and Mediates Specific Killing of Tumor Cells

Abstract: Natural killer (NK) cells are highly specialized effectors of the innate immune system that hold promise for adoptive cancer immunotherapy. Their cell killing activity is primarily mediated by the pro-apoptotic serine protease granzyme B (GrB), which enters targets cells with the help of the pore-forming protein perforin. We investigated expression of a chimeric GrB fusion protein in NK cells as a means to augment their antitumoral activity. For selective targeting to tumor cells, we fused the epidermal growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…To date there are no reports on gene dosage effects regarding granzyme B, although it has been suggested that altered granzyme B expression contributes to increased tumor cell surveillance. 35,36 Interestingly, the amount of granzyme B protein was increased without a concomitant change in the level of mRNA, suggesting the involvement of microRNAs. Both perforin and granzyme B have been described as targets of microRNA-dependent regulation in NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…To date there are no reports on gene dosage effects regarding granzyme B, although it has been suggested that altered granzyme B expression contributes to increased tumor cell surveillance. 35,36 Interestingly, the amount of granzyme B protein was increased without a concomitant change in the level of mRNA, suggesting the involvement of microRNAs. Both perforin and granzyme B have been described as targets of microRNA-dependent regulation in NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of recombinant immunotoxins has been extensively investigated in the field of targeted tumor therapy with various bacterial and human effector domains (30)(31)(32), including Gb (11,13,27,33). After binding to a disease-specific cell surface antigen, these immunotoxins are internalized, e.g., by receptor-mediated endocytosis, released from endosomal compartments into the cytoplasm, and efficiently kill the malignant cell by their catalytic activity.…”
Section: Figmentioning
confidence: 99%
“…102 Finally, to better protect NK cells from the NK cell-inhibitory cytokine TGFβ, NK cells (NK-92) were genetically modified to express a dominant negative TGFβ receptor designed to neutralize TGFβ signaling. These cells were rendered resistant to the suppressive effects of the cytokine and were able to mediate antitumor activity.…”
mentioning
confidence: 99%